2015
DOI: 10.1038/bjc.2015.127
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis of metastatic breast cancer: are there differences between patients with de novo and recurrent metastatic breast cancer?

Abstract: Background:We aimed to determine the prognostic impact of time between primary breast cancer and diagnosis of distant metastasis (metastatic-free interval, MFI) on the survival of metastatic breast cancer patients.Methods:Consecutive patients diagnosed with metastatic breast cancer in 2007–2009 in eight hospitals in the Southeast of the Netherlands were included and categorised based on MFI. Survival curves were estimated using the Kaplan–Meier method. Cox proportional hazards model was used to determine the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

32
163
4
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 203 publications
(203 citation statements)
references
References 25 publications
32
163
4
4
Order By: Relevance
“…However, although the difference in the prognostic outcomes of metastatic diseases between de novo and recurrent BC patients is still unclear, these patients have often been treated using the same strategy. Previous reports have indicated that de novo BC patients have better survival than recurrent BC patients (10)(11)(12), and our study also confirms these results. Metastatic BC forms heterogeneous groups with varying prognostic outcomes, requiring the development of a distinct treatment approach for each BC subtype (14)(15)(16).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…However, although the difference in the prognostic outcomes of metastatic diseases between de novo and recurrent BC patients is still unclear, these patients have often been treated using the same strategy. Previous reports have indicated that de novo BC patients have better survival than recurrent BC patients (10)(11)(12), and our study also confirms these results. Metastatic BC forms heterogeneous groups with varying prognostic outcomes, requiring the development of a distinct treatment approach for each BC subtype (14)(15)(16).…”
Section: Discussionsupporting
confidence: 91%
“…BC patients who experienced a distant recurrence within or soon after adjuvant treatment may present with therapeutic resistance, also leading to poorer prognostic outcomes. In contrast, de novo disease is therapy-naive, and therefore likely to show less resistance to systemic therapy (10)(11)(12). BC patients with longer DFI or patients who developed a distant recurrence some years after adjuvant treatment may have a better response to systemic therapy.…”
Section: Discussionmentioning
confidence: 99%
“…11 As a result, some cases that might have been assigned as stage IIIc in countries that adhered to criteria in the sixth 10 Overall, the proportion of patients in this study with known HR status who had a primary diagnosis of HR-positive LA/MBC was lower (7.8%) than in previously published estimates (approximately 13%-17%). [6][7][8] However, the generalizability of the previous findings is limited, because they were derived from a small number of patient records. In addition, the range of years and geographic regions included in these studies differed from the present study, and comparisons should therefore be interpreted with caution.…”
Section: Esther Bastiaannet Et Almentioning
confidence: 99%
“…Studies of small retrospective databases have reported that of all patients with known HR status, approximately 13% to 17% had a primary diagnosis of HR-positive advanced disease (LA/MBC). [6][7][8] However, these studies did not assess subsequent therapy in this patient group, and, to our knowledge, a comprehensive evaluation of the size of this patient population has not been performed.…”
Section: Introductionmentioning
confidence: 99%
“…19 O sítio de metástase é um fator prognóstico independente para a sobrevida das mulheres com neoplasia maligna da mama. [16][17][18][19][20][21][22] No Brasil, embora alguns autores tenham avaliado a sobrevida do cân-cer de mama segundo a presença de metástase à distância, 23,24 ainda pouco se abordou essa questão no que se refere aos sítios metastáticos acometidos. Vale lembrar que, além de investigarem o impacto de características inerentes ao tumor, os dados de sobrevida são o parâmetro mais utilizado para avaliar resultados na área oncológica, permitindo identificar avanços diagnósticos e terapêuti-cos, bem como analisar a eficiência global do controle do câncer pelo sistema de saúde.…”
Section: Introductionunclassified